2008
DOI: 10.1158/0008-5472.can-08-0020
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of P-Cadherin Correlates with Promoter Hypomethylation Early in Colorectal Carcinogenesis and Enhanced Intestinal Crypt Fission In vivo

Abstract: P-cadherin is normally expressed in the basal layer of squamous epithelia and absent from the healthy intestine and colon. We have previously shown it to be expressed in all inflamed, hyperplastic, and dysplastic intestinal and colonic mucosa. This study aimed to better understand the mechanisms controlling the expression of P-cadherin and the biological effects of its ectopic presence in the intestine and colon. We investigated the CpG methylation status of the P-cadherin (CDH3) promoter and P-cadherin mRNA a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 41 publications
3
48
0
Order By: Relevance
“…Reinforcing our results, CDH3 promoter was also found hypomethylated in colonic aberrant crypt foci, in colorectal cancer, and, occasionally, in the normal epithelium adjacent to cancer (Milicic et al, 2008). This hypomethylation pattern was associated with the induction of P-cadherin expression in the neoplastic colon.…”
Section: Epigenetic Regulation Of P-cadherin Expressionsupporting
confidence: 88%
“…Reinforcing our results, CDH3 promoter was also found hypomethylated in colonic aberrant crypt foci, in colorectal cancer, and, occasionally, in the normal epithelium adjacent to cancer (Milicic et al, 2008). This hypomethylation pattern was associated with the induction of P-cadherin expression in the neoplastic colon.…”
Section: Epigenetic Regulation Of P-cadherin Expressionsupporting
confidence: 88%
“…The role of P-cadherin in colorectal carcinogenesis has not been extensively studied, however, its increased expression has previously been reported based on immunohistochemical staining of AD (12) and AC (13). P-cadherin is classified as an oncogene due to its ability to increase crypt cell proliferation in the context of inflammation (14). In addition, two reports have suggested that CDH3 upregulation in cancer tissue is associated with gene promoter demethylation (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…P-cadherin is classified as an oncogene due to its ability to increase crypt cell proliferation in the context of inflammation (14). In addition, two reports have suggested that CDH3 upregulation in cancer tissue is associated with gene promoter demethylation (14,15). However, using a quantitative approach, increased promoter hypomethylation was identified in only 77% of carcinomas (15), which does not account for the universal upregulation of the expression of this gene in AD and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Crypt fission is of interest because it represents increased stem cell clonal expansion in intestinal dysplasia and models of familial adenomatous polyposis (40,46).…”
Section: Discussionmentioning
confidence: 99%